Blood-Brain Barrier Transport of Drugs for the Treatment of Brain Diseases - Gabathuler, Reinhard (CNS & Neurological Disorders - Drug Targets, 2009)
The central nervous system is a sanctuary protected by barriers that regulate brain homeostasis and control the transport of endogenous compounds into the brain. The blood-brain barrier, formed by endothelial cells of the brain capillaries, restricts access to brain cells allowing entry only to amino acids, glucose and hormones needed for normal brain cell function and metabolism. This very tight regulation of brain cell access is essential for the survival of neurons which do not have a significant capacity to regenerate, but also prevents therapeutic compounds, small and large, from reaching the brain. As a result, various strategies are being developed to enhance access of drugs to the brain parenchyma at therapeutically meaningful concentrations to effectively manage disease.
Keywords: therapies